“Is Aphorism Reviving Thanks To Twitter?” – Short Forms on the Internet - Lay Brander, Miriam (Meridional. Revista Chilena de Estudios Latinoamericanos, 2015)
The article deals with the influence of the internet on contemporary aphorism in the Spanish language by asking how the characteristics of this genre show its adaptation to digital media. Based on micro texts created by both amateurs and known writers or users it answers this question in terms of the artistic and folk quality of short forms on the internet as well as their degree of interactivity and intermediality. As we will see, manifestations of aphorism on the web give an example of how digitalization contributes to deconstruct the modern Western concept of literature. This is not only done by fragmenting, pluralizing and democratizing authorship but also by connecting learned to popular culture and written to oral forms.